Rumen-protected glucose supplementation alters fecal microbiota and its metabolic profiles in early lactation dairy cows - Wang, Yapin; Zhao, Yiguang; Nan, Xuemei; Wang, Yue; Cai, Meng; Jiang, Linshu; Luo, Qingyao; Xiong, Benhai (Frontiers in Microbiology, 2022)
Negative energy balance (NEB) is the pathological basis of metabolic disorders in early lactation dairy cows. Rumen-protected glucose (RPG) is a feed additive to relieve NEB of cows in early lactation. The aims of the current study were to evaluate the impact of different doses of RPG supply on fecal microbiota and metabolome in early lactation dairy cows, and their correlation with each other. A total of 24 multiparous Holstein dairy cows in early lactation were randomly assigned to one of four treatments for the first 35 days of early lactation period, as follows: control group, a basal diet without RPG (CON); low RPG, a basal diet plus 200 g/d RPG (LRPG); medium RPG, a basal diet plus 350 g/d RPG (MRPG); or HRPG, high RPG, a basal diet plus 500 g/d RPG (HRPG). After 35 days, fecal samples were obtained from cows in all groups individually, and using 16S rRNA gene sequencing to evaluate their microbiotas, while their metabolites were evaluated through metabolomics. As expected, Firmicutes and Bacteroidetes were the core bacteria phyla. After RPG supplementation, there were an increase in Firmicutes and a decrease in Bacteroidetes. MRPG increased the relative abundance of cellulolytic bacteria, including Ruminococcaceae_UCG-005, Lachnospiraceae_UCG-008, Lachnospiraceae_FCS020_group, and Ruminiclostridium_9, while decreased the relative abundance of Alistipes, Prevotellaceae_UCG-003, and Dorea. RPG supplementation could regulate the carbohydrate metabolism and amino acid metabolism pathway significantly, relieve lipolysis in dairy cows. Correlation analysis of fecal microbiome and metabolome showed that some major differential bacteria were the crucial contributors to differential metabolites. In conclusion, RPG supplementation can affect the fecal microbial components and microbial metabolism, and 350 g RPG might be the ideal dose as a daily supplement.